Linien - Gesten - Bücher zu Henri Michaux - Mainberger, Sabine 1960- (De Gruyter, 2020)
This study focuses on various scenes of calligraphy, practices and conceptualizations of lines, and questions of book aesthetics in Henri Michaux's pictorial, literary oeuvre. The theoretical horizon is provided by current approaches to knowledge of the body and motion, kinesthesia, habitus, body-memory, et al. in anthropology and the social sciences. In the twofold break with traditional functions of the graphic line and the notation function of text, the emphasis here is on writing as a body technique and performance as well as improvised graphic records. An art of the motoric is nevertheless encountered in the form of books and generally combined with texts. Problems of approaching "Western" and Chinese (text) art are also discussed from a praxeological perspective
Keywords: Michaux, Henri -- 1899-1984; Henri Michaux; Kunst; Schrift; ART / Individual Artists / General